The Use of Electronic Signatures and Seals in Notarial Deeds According to the Principle of Tablelionis Officium Fideliter Exercebo - Nisrina Anrika Nirmalapurie; Fransiscus Xaverius Arsin (IHSA Institute, 2022)
The notary as the official authorized to make authentic deeds in carrying out his duties must work traditionally due to the principle of Tabellionis Officium Fideliter Exercebo. Technological developments and the needs of the community make making agreements today easier and more concise, namely by using electronic signatures and seals in an agreement. The question that arises from this background is whether the use of electronic signatures and seals is under the principle adopted by a notary, namely the Tabellionis Officium Fideliter Exercebo principle. The result of this research is that the use of electronic signatures cannot be applied because the legislation does not allow certified digital signature on notarial deeds so the use of digital signatures on notarial deeds is not following the principle of the Tablelionis Officium Fideliter Exercebo, while the use of electronic seals can be carried out and does not conflict with this principle because apart from the stamp duty, it is not a requirement for the validity of a deed, the use of an electronic seal in a notarial deed is also possible under the Stamp Duty Act.